EP416 Large conization: an effective surgical approach for fertility preservation in young women with early stage cervical cancer. (1st November 2019) - Tsaousidis, C; Taran, F-A; Kommoss, S; Hartkopf, A; Brucker, SY; Kraemer, B
Abstract : Introduction/Background: The shorter cervical segment after radical trachelectomy (RT) imposes a number of pregnancy-associated risk factors. Large conization (LC) can therefore be an oncologically safe alternative to RT in young women with early stage cervical cancer who want to keep their fertility. Our aim was to evaluate fertility-sparing surgical treatment of early-stage cervical cancer after the introduction of LC. Our objectives were to assess surgical, oncological, fertility, and obstetric outcomes. Methodology: We followed up the oncological and fertility outcomes of patients who underwent LC in a large oncological single University center between 2009 and 2014. Medical records were reviewed and analyzed for surgical, oncological, fertility, and obstetric outcomes. Postal questionnaires were collected to further evaluate and validate the fertility and obstetric outcomes. Results: A total of 24 LC's were analyzed. Eight patients had to undergo secondary radical hysterectomy after the LC because of non in sano resection. Nine of 16 women tried to conceive, of which all nine became pregnant. Seven mothers gave birth to nine children; The majority of women conceived spontaneously. Conclusion: Early-stage cervical cancers treated by LC are associated with acceptable oncological outcomes. LC appears to be a safe option for eligible women who intend to maintain their wish for a future pregnancy. Disclosure: Nothing to disclose.